GOAL SETTING AS A MOTIVATOR OF UNETHICAL BEHAVIOR. - Schweitzer, M. E.; Ordonez, L.; Douma, B. (Academy of Management Journal, 2004)
We explored the role of goal setting in motivating unethical behavior in a laboratory experiment. We found that people with unmet goals were more likely to engage in unethical behavior than people attempting to do their best. This relationship held for goals both with and without economic incentives. We also found that the relationship between goal setting and unethical behavior was particularly strong when people fell just short of reaching their goals. A substantial literature has documented the benefits of setting goals. In general, people exert more effort and work more persistently to attain difficult goals than they do when they attempt to attain less difficult goals or to “do their best” (Locke & Latham, 1990). This relationship is so strong that goal setting has become an important part of motivation theory and management education (Ambrose & Kulik, 1999). In fact, Locke and Latham (1990) contended that goal setting might be the most effective managerial tool available. In several organizational settings, however, the use of goal setting has been associated with “cooked books” and false sales reports (e.g., Degeorge, Patel, & Zeckhauser, 1999; Jensen, 2001). In this work, we identify an important, unintended consequence of setting goals. Our results demonstrate that, in addition to motivating constructive effort, goal setting motivates unethical behavior when people fall short of their goals. We argue that while goal setting can be used constructively, it must also be used cautiously.